Arsitektur Ekologi Dengan Pendekatan Lingkungan dan Origami Pada Perancangan Gamat Bay Glamping: Bahasa Indonesia - I Nyoman Andy Armawan; Ida Bagus Gede Parama Putra; I Ketut Sugihantara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
In the current era, tourism is crucial to the development of the Balinese economy. Reflecting on the pandemic that has been going on for the past few years, Bali tourism has experienced a very significant impact. Currently, Bali tourism is slowly starting to rise, and as Balinese people, we should play a role and support the rebuilding, especially in the tourism sector. In fact, tourism is the identity of the island of Bali, with its own charm. One of the accommodations that can boost Bali tourism is beach glamping. The planning and design of Gamat Bay Glamping in Nusa Penida, Klungkung, uses the Envi-Human Connection concept. Natural factors can give Nusa Penida more points because Nusa Penida already has its own charm that other regions don't even have, namely its natural beauty. Related to tourism, of course, you can never get away from tourists. In realizing the concept raised, namely Envi-Human Connection, whatever the design theme of the planning and design of Gamat Bay Glamping in Nusa Penida, Klungkung, is ecological architecture with environtmental and origami approach.